Prevalence and factors associated with thirst among postsurgical patients at University of Gondar comprehensive specialized hospital. Institution-based cross-sectional study - Kumlachew Geta Belete; Henos Enyew Ashagrie; Misganaw Mengie Workie; Seid Adem Ahmed (SpringerOpen, 2022)
Abstract Introduction Thirst is a powerfully distressing sensation that occurs most frequently in the immediate postoperative period. Postoperative thirst is prevalent, the moderate-to-severe type is estimated to affect 53.2-69.8% of patients and causes significant patient discomfort. Objective The objective of this study was to assess the prevalence, and factors associated with postoperative thirst among surgical patients in PACU at the University of Gondar Comprehensive Specialized Hospital from April 20 to June 27, 2021. Methods An institution-based cross-sectional study was conducted at the University of Gondar Comprehensive Specialized Hospital. A total of 424 participants were included in the study. Statistical analysis had performed using SPSS 26.00 version statistical software. Binary logistic regression analysis was performed to identify the association between the prevalence of postoperative thirst and independent variables and only variables with p-value < 0.2 were entered into the multivariable analysis. The strength of the association was presented by odds ratio and 95% Confidence interval. P-value < 0.05 was considered statistically significant. Result The prevalence of postoperative thirst among postsurgical patients was 59% (95% CI = 54.74-64.13). Inadequate preloading (Adjusted odes ratio (AOR) = 2.137 95% CI 1.260-3.624), prolonged Nil Per Os (NPO) time (AOR = 13.80 95% CI 2.93-65.37), general anesthesia (AOR = 3.90 95% CI 3.56-11.25), and axillary body temperature ≥ 37.5 °C (AOR = 8.07 95% CI 3.63-17.96) were significantly associated with postoperative thirst. Low room temperature (< 20 °C) was protective for the occurrence of postoperative thirst (AOR = 0.162 95% CI 0.37-0.707). Conclusion and recommendations The prevalence of postoperative thirst remains high and need commitment in close monitoring of PACU patients and immediate intervention. We also urge that high-level, ongoing research be conducted in this area, as postoperative thirst is a very common problem with a lot to discover.